Corrigendum: “Electrodiagnostic assessment of the autonomic nervous system: A consensus statement endorsed by the American Autonomic Society, American Academy of Neurology, and the International Federation of Clinical Neurophysiology” (Clinical Neurophysiology (2021) 132(2) (666–682), (S138824572030585X), (10.1016/j.clinph.2020.11.024)) - Cheshire, William P.; Freeman, Roy; Gibbons, Christopher H.; Cortelli, Pietro; Wenning, Gregor K.; Hilz, Max-Josef; Spies, Judith M.; Lipp, Axel; Sandroni, Paola; Wada, Naoki; Mano, Tadaaki; Kim, Hyun Ah; et al. (Clinical Neurophysiology, 2021)
The authors would like to inform you that the name of the 11th author, Tadaaki Mano, was incorrectly stated as Akiko Mano in their published article. The correct details updated as above. The authors apologise for this error.
CRIS-Team Scopus Importer:2021-03-26